Molecular Characterization of Four (4) Accessions Sesame (Sesamum indicum L.) Cultivated in Different Localities of Central Africa and the Pakréssaya Variety (of Burkinabe Origin) - (:unkn) unknown (My University, 2025)
Sesame (Sesamum indicum L) is probably the oldest oilseed crop known and used by humans. In the Central African Republic, sesame remains an “orphan crop” due to the lack of scientific data on the genetic diversity of local accessions. Genetic diversity is the extent of genetic variability measured at the level of individuals, a population, a metapopulation, a species or a group of species. It is ensured by the genetic variability between individuals within the species. This study aims to contribute to a better knowledge of the genetic characteristics of sesame accessions in the Central African Republic. Analyses included genome sequence analysis and genetic polymorphism. Total DNA was extracted using the Zymo Research Kit, taking for each accession or variety a pool of five seeds constituting an individual. The results obtained showed the effectiveness of the 28S gene for the differentiation of sesame accessions (Sesamum indicum) because it showed a significant polymorphism between the different accessions studied and the Pakréssaya variety. The phylogenetic trees allowed us to structure sesame seeds according to their locality of origin.
Keywords: African Research